Management of Medical Record Unit to Preparing Accreditation at Primary Health Care - Faizah Wardhina; Ermas Estiyana (Global Health Science Group, 2020)
Puskesmas as the spearhead of public health services are required to always improve the quality of service delivery, both in the administration of primary health care management, clinical services, and primary health care program services. Accreditation is one of the efforts to ensure the quality improvement of primary health care services. Primary health care must compile medical records in accordance with the standards and criteria set by the first level health facility accreditation commission. It becomes a problem if the Puskesmas does not yet have human resources in the field of medical records, included the Karang Intan 2 primary health care. For this reason, primary health care need to increase the knowledge of its officers about managing medical record units and health information. The purpose of this community service activity is to increase the knowledge and skills of officers in managing the medical record unit at the Karang Intan 2 primary health care. This method of community service activities is carried out by provided learning about medical records to three medical record officers, then continued with guidance and consultation as well as monitored and evaluation to ensure a change for the better in the management of the medical record unit at the Karang Intan 2 primary health care. The result of this activity was an increased in the knowledge and skills of the medical record unit officers.